“I Just Can’t Take It Anymore”: How Specific Work Characteristics Impact Younger Versus Older Nurses’ Health, Satisfaction, and Commitment - Van der Heijden, Beatrice I. J. M.; Houkes, Inge; Van den Broeck, Anja; Czabanowska, Katarzyna (Frontiers in Psychology, 2020)
Given the increasing shortage of active nurses in industrialized countries throughout the world, it is of utmost importance to protect their health, satisfaction and commitment so that they can continue working in their healthcare institution. Building upon the proposed pattern of specific relationships developed by Houkes, Janssen, De Jonge and Bakker (2003), we investigated a model of relationships among working conditions (quantitative, emotional, and physical demands), labor relations (quality of interpersonal relations and psychological support), work content (meaning of work, influence at work), and employment conditions (opportunities for development) on the one hand, and health, job satisfaction and institutional affective commitment on the other hand, for younger versus older nurses. We used data of 3,399 nurses from the Netherlands and 3,636 nurses from Poland from the larger European Nurses’ Early Exit Study (NEXT), and performed longitudinal Structural Equation Modelling and Multi-Group Analyses. The results showed that the proposed pattern of relationships generally holds, but that the nurses’ level of commitment is more determined by meaning of work than by opportunities for development, and that psychological support is associated with job satisfaction (and not only with burnout as hypothesized, in both the Netherlands and Poland). Comparing younger (< 40 years) versus older (≥ 40 years) nurses, we found ample support for differences in the proposed model relationships across age category, some being in line and some being contradictory to our expectations. We argue that a non-normative, tailor-made approach to ageing at work might help us to protect the nurses’ career sustainability across the life-span. This study provides evidence-based practical recommendations on how to enhance the health, job satisfaction and commitment of nurses throughout their working life. Key words: nurses, working conditions, labor relations, work content, conditions of employment, burnout, disability, job satisfaction, institutional affective commitment, age